Evaluating audio-visual and computer programs for classroom use. - Van Ort S (Nurse Educator)
Appropriate faculty decisions regarding adoption of audiovisual and computer programs are critical to the classroom use of these learning materials. The author describes the decision-making process in one college of nursing and the adaptation of an evaluation tool for use by faculty in reviewing audiovisual and computer programs.